The moderating role of barriers to agility and their impacts on organisational performance - Mohamed Rahim, Siti Nur Syuhada; Kamarulzaman, Nitty Hirawaty; Mohd Nawi, Nolila; Abdul Hadi, Ahmad Hanis Izani (Human Resource Management Academic Research Society, 2024)
Competing in fast-changing environments requires organisations to be more agile. However, barriers to agility hinder an organisation’s ability to enhance its responsiveness in decision-making processes and performance. This study investigates the impact of agility and barriers to agility on organisational performance and the moderating role of barriers to agility on the relationship between agility and organisational performance. Resource-Based View (RBV) and Contingency Theory were implied by using a quantitative deductive reasoning methodology. Data were collected via interviews. The stratified random sampling technique was employed to choose 153 oil palm plantation executives. Key findings revealed that agility positively impacts organisational performance (β = 0.243). However, barriers to agility were found to negatively impact organisational performance (β = -0.013). Further analysis also revealed that the moderating effect of barriers to agility caused an effect on the positive relationship between agility and organisational performance (β = -0.230). The effect of barriers to agility also changed the relationship between agility and organisational performance’s positive direction to negative. This study concludes that barriers to agility hinder an organisation’s agility. Addressing these barriers is crucial for organisations to fully leverage the potential of agility and achieve higher performance levels in a dynamic and competitive business environment.